Activin B antagonizes RhoA signaling to stimulate mesenchymal morphology and invasiveness of clear cell renal cell carcinomas - Wacker, Ingrid; Behrens, Jürgen (PLoS ONE, 2014)
Activin B belongs to the TGF? family of growth factors and is upregulated in clear cell renal cell carcinoma cells by hypoxia inducible factors. Expression of Activin B is required for tumor growth in vivo and tumor cell invasion in vitro. Here we show that activation of RhoA signaling counteracts Activin B mediated disassembly of actin stress fibers, mesenchymal cell morphology and invasiveness, whereas inhibition of RhoA rescues these effects in Activin B knockdown cells. Conversely, Activin B inhibits RhoA signaling suggesting that there is an antagonistic connection between both pathways. In addition we found that Rac1 plays an opposite role to RhoA, i.e. activation of Rac1 initiates loss of actin stress fibers, promotes a mesenchymal cell morphology and induces invasion in Activin B knockown cells, whereas inhibition of Rac1 abolishes these Activin B effects. Collectively, our data provide evidence that reduction of RhoA signaling by Activin B together with persistent Rac1 activity is a prerequisite for inducing an invasive phenotype in clear cell renal cell carcinoma.
EVALuna2:10307